Optimizing efficacy of mucosal vaccines. (September 2012) - Gebril, Ayman; Alsaadi, Manal; Acevedo, Reinaldo; Mullen, Alexander B; Ferro, Valerie A
In general, there are only a few vaccines administered via mucosal routes, as the mucosal immune system presents numerous hurdles, including diversity in mucosal surface structure, complexity in immune cell interaction and limitations in experimental methodology. This therefore necessitates a range of strategies to be used for each target area. With reference to the three main routes of delivery and associated mucosal surfaces (oral/intestinal, nasal/respiratory and female genital tract), this review examines how coadministration of immune-stimulatory molecules, adjuvants, delivery systems and mucoadhesives are used to improve mucosal vaccine efficacy. Key considerations to the development of next-generation mucosal vaccines include improved efficacy and safety, technological advancements in medical devices to enable convenience and better administration, as well as reduced manufacturing costs.